PENGEMBANGAN DONGENG BERBENTUK VIDEO ANIMASI UNTUK ANAK USIA 5-6 TAHUN DI TK NEGERI PEMBINA 2 PALEMBANG - Ela Paramita; Hasmalena hasmalena; syafdaningsih syafar (Tumbuh Kembang: Kajian Teori dan Pembelajaran PAUD, 2019)
This research aims to produce a fairy tale in a form of animated video. Development of this fairy tale in a form of animated video uses a combination of ADDIE development model and Tessmer evaluation. The ADDIE development model consists of five phases namely the analysis phase, the design phase, the development phase, the implementation phase and the evaluation phase. At the evaluation phase, the formative is proposed by Tessmer consisting of four stages namely self-evaluation stage, expert review stage, one-to-one evaluation and small group evaluation. The data is collected by using an observation technique. The result of the expert review with the suggestion given by the experts in the story content has been appropriate for the children aged 5-6 years as well as the theme and the language with a good average assesment score with a valid average result of 3.75 (very valid category) and any suggestions given by the experts are the cover of that animation, interesting design, a very good music for the video and the illustration of the story in that aninated video is giving a good time for the children, and it is not borung at all which the average score of 4,00% (very valid catagory). An average for the experts validation for the development of a fairy tale in a form of animated video is 3,87% (very valid category). At the stage of one to one evaluation using a 3 child samples viewing a tale in form of animated video with an average of 91.7% (very practical category). The small group evaluation stage of this fairy tale in form of animated video obtained an average yield of 88.3% in average (very practical category). From all stages that have been done can be concluded that the fairy tale in a form of animated video is valid and practical for children.